The mentally retarded offender in the criminal justice system - Montgomery, Reid H. (American journal of criminal justice, 1982)
The problem of the mentally retarded offender begins at the first encounter with the criminal justice system and continues through the correctional system. A recent survey compared attitudus of police and mental health professional. Police (78%) felt that disturbed person (including mentally retarded offenders) should be handcuffed when being transported. In contrast, mental health professionals (84%) felt no individual should be handcuffed. The mentally retarded offenders, once incarcerated, are a group that is confronted with problems beyond those usually associated with prison life. The authors examine the complex issued stemming from the special conditions of the MRO and suggest recommendations for developing rational attitudes and policies within the criminal justice system.